The effect of implementing content and language integrated learning method (CLIL) on the writing performance of learners of english as a foreign language: the case of Nguyen Thi Minh Khai high school : - Thái, Nguyễn Tường Vi (Đại Học Cần Thơ, 2013)
The current research is aimed at examing the effect of implementing CLIL on EFL learners' writing performance. It also seeks to explore which aspect of writing performance is most influenced by CLIL method.